Repeated Sprint Ability in Young Basketball Players: Multi-direction vs. One-Change of Direction (Part 1) - Padulo, Johnny; Bragazzi, Nicola L.; Nikolaidis, Pantelis T.; Dello Iacono, Antonio; Attene, Giuseppe; Pizzolato, Fabio; Dal Pupo, Juliano; Zagatto, Alessandro M.; Oggianu, Marcello; Migliaccio, Gian M. (Frontiers in Physiology, 2016)
The aim of the present study was to examine the reliability of a novel multi-direction repeated sprint ability (RSA) test [RSM; 10 × (6 × 5-m)] compared with a RSA with one change of direction [10 × (2 × 15-m)], and the relationship of the RSM and RSA with Yo-Yo intermittent recovery test level 1 (Yo-Yo IR1) and jump performances [squat jump (SJ) and counter-movement-jump (CMJ)]. Thirty-six (male, n = 14, female n = 22) young basketball players (age 16.0 ± 0.9 yrs) performed the RSM, RSA, Yo-Yo IR1, SJ, and CMJ, and were re-tested only for RSM and RSA after 1 week. The absolute error of reliability (standard error of the measurement) was lower than 0.212 and 0.617-s for the time variables of the RSA and RSM test, respectively. Performance in the RSA and RSM test significantly correlated with CMJ and SJ. The best time, worst time, and total time of the RSA and RSM test were negatively correlated with Yo-Yo IR1 distance. Based on these findings, consistent with previously published studies, it was concluded that the novel RSM test was valid and reliable.